Using design of experiment to evaluate changes to the characteristics of 6-nitroBIPS - Wahid, Zaharah; Nadir, Najiah (2014)
Recently, there is a growing interest in the area of designing and synthesis of functional dye molecules that can serve as molecular devices for sensors, photo -switching and signal transduction. Among photochromic compounds that could be used for such purpose are spiropyrans. This paper presents a statistical experimental of design approach to evaluate the impact of so lvent polarity, durations of ultraviolet(UV) exposure and dye concentration variables on 6-nitro-1’,3’,3’-trimethylspiro[2H-1-benzopyran-2, 2’] (6-Nitro BIPS). Through this approach the impact of a given change on the behavior of the 6-Nitro BIPS could be measured with reduced number of experiments. Three variables at 2-level setting were used in this investigation. Analysis of variance (ANOVA) is employed to analyze the results. The results obtained highlighted that concentration and solvent polarity are the most significant variables. In addition this study shows that the interaction effect between the concentration and solvent variables is essential for insightful interpretation of results and effective decision making.